Experiments with economic principles : microeconomics - Bergstrom, Theodore C.; Miller, John H. (Boston : McGrw-Hill / Irwin, 2000)
Economics
2003-04-16
Keywords: Economics; Supply; Demand; Public policy; Firms; Wages; Auctions; Economic principles